Strengthening and Developing Digital Learning Media to Support SDGs Quality Education at PAUD Bungong Seurune: Penguatan dan Pengembangan Media Belajar Digital untuk Mendukung SDGs Pendidikan Berkualitas di PAUD Bungong Seurune - Maulida, Maulida; Samsuar, Samsuar; Rini Susiani; Rachmah Putri Salsabila; Nurul Qolbiya (Universitas Lancang Kuning, 2024)
PAUD Bungong Seurune is one of the institutions for organizing and caring for early childhood children with NSPN 69807316 which is located at Mosque No. 3, Gampong Tungkob, District. Darussalam, Kab. Aceh Besar Province Aceh. The number of students at PAUD Bungong Seurune is 25 students and 10 teachers. Bungong Seurune PAUD does not yet have adequate learning media, especially learning media that uses information technology in the form of applications that can help teachers in the learning process. This service focuses on developing digital learning media by combining literacy and numeracy combined with simple English so that the learning process becomes more interesting and enjoyable. The method used in the service program includes 5 stages, namely, socialization, training, application of technology, mentoring and evaluation, and program sustainability. With the development of digital learning media for Bungong Seurune PAUD teachers, it is hoped that it will be able to increase literacy and learning media used in the learning process. The learning media that has been designed has added simple English so that the media produced will be much more interesting and useful.